PENGARUH KEPEMIMPINAN DAN PENGELOLAAN SUMBER DAYA MANUSIA TERHADAP KINERJA DI DINAS LINGKUNGAN HIDUP KOTA DUMAI - Yuliana Safitri; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out at the Dumai City Environmental Agency. With the aim of measuring the influence of leadership and management of human resources on performance in the Department of Environment of Dumai City. The sample in this study were all employees of the Department of Environment of Dumai City, amounting to 64 people taken using the census method. Data is taken from the questionnaire on the object under study and other reports. Processing data in this study uses a multiple linear regression analysis test with the SPSS program. Based on the results of statistical tests, several conclusions can be drawn, namely that leadership in the Department of Environment of Dumai City is quite good with an average score of 207 which is in the range of 168-219 with a fairly good category, human resource management in the Dumai City Environmental Service relatively good with an average score of 208 which is in the scale range 168-219 with a fairly good category and the performance in the Department of Environment of Dumai City is quite good with an average score of 209 located in the scale range 168-219 with the category pretty good. Leadership and management of human resources have a significant effect on the performance of the Department of Environment in Dumai City with the degree of closeness of the relationship in the very strong category. Based on the test results simultaneously, F count (329,074)> F table (3,15) with Sig. (0,000) <0.05. The meaning is that the independent variables (leadership and management of human resources) together have a significant effect on the dependent variable (performance). Then H0 is rejected and Ha is accepted. Based on the partial test results, the most influential variable on performance is the leadership variable with t count (8.121)> t table (1,999) with Sig. 0,000 <0,05. This means that leadership variables have a significant effect on performance.Keywords: Leadership, Management of Human Resources, Performance